1991
DOI: 10.1002/1097-0142(19910215)67:4<939::aid-cncr2820670414>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric dna analysis of hepatocellular carcinoma

Abstract: The prognostic value of nuclear DNA content was studied retrospectively using flow cytometry in 203 cases of resected hepatocellular carcinoma. The occurrence of DNA aneuploidy, which was detected in 50% of patients, correlated significantly with tumor size and the presence of vascular invasion or intrahepatic metastasis. Overall, patients with DNA aneuploid tumors had a significantly worse prognosis than those with DNA diploid tumors (P < 0.001) and, also in subdivided groups by tumor size (P < 0.01). Among D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
1

Year Published

1993
1993
2006
2006

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(47 citation statements)
references
References 26 publications
1
45
1
Order By: Relevance
“…Genetics of hepatocellular tumors P Laurent-Puig and J Zucman-Rossi in tumor cells suggesting a global gain of genetic material, in half of the analysed HCC cases (Ezaki et al, 1988;Fujimoto et al, 1991;Chiu et al, 1992). Hyperploidy is also found in 43% of dysplastic lesions observed in cirrhotic disease (Thomas et al, 1992).…”
Section: Genetic Alterations Not Related To Etiological Factorsmentioning
confidence: 99%
“…Genetics of hepatocellular tumors P Laurent-Puig and J Zucman-Rossi in tumor cells suggesting a global gain of genetic material, in half of the analysed HCC cases (Ezaki et al, 1988;Fujimoto et al, 1991;Chiu et al, 1992). Hyperploidy is also found in 43% of dysplastic lesions observed in cirrhotic disease (Thomas et al, 1992).…”
Section: Genetic Alterations Not Related To Etiological Factorsmentioning
confidence: 99%
“…It has been shown that DNA content analysis is an important predictor of prognosis, which is better in diploid than in aneuploid tumours (Fujimoto et al, 1991;Chiu et al, 1992), although some authors have suggested that the advanced tumour stage of large lesions may negate the influence of DNA ploidy status on patient outcome (McEntee et al, 1992). These studies were limited to analysis of a single tumour nodule in patients with HCC.…”
Section: Resultsmentioning
confidence: 97%
“…Quantitative DNA analysis reflects the total chromosomal content of tumour cells. In terms of the cell nuclear DNA content of HCC, it has been reported (Fujimoto et al, 1991;Chiu et al, 1992) that an aneuploid DNA pattern indicates poor prognosis. With regard to the heterogeneity of the DNA ploidy pattern, HCC has been reported to be mostly homogeneous within the same tumour (Kuo et al, 1987;Nagasue et al, 1993;Ng et al, 1994).…”
mentioning
confidence: 99%
“…Furthermore, the autocrine mechanism of EGF and EGF-R could be one of the contributory factors on the development of DNA abnormalities during tumor proliferation. intratumoral heterogeneity; cytofluorometry; immunohistochemistry; esophageal carcinoma With the aid of flow cytometry and cytofluorometry, the determination of the DNA content in various types of tumors (Sannohe and Hiratsuka 1981;Sugimachi et al 1986;Heikki et al 1990;Sing et al 1990;Fujimoto et al 1991) has been widely carried out to evaluate the degree of malignancy and prognosis. Compared with the flow cytometry, the cytofluorometry has been reported to have more advantage to measure the DNA content in specific target cells and to provide more accurate results from small tissue samples (Cusic et al 1990).…”
mentioning
confidence: 80%
“…Although enough number of examined cases were available in this study, the present results seem to be compatible with the idea that multiple DNA types develop during carcinogensis (Rabinovitch et al 1988;Mckinley et al 1987). Furthermore, we speculate that the cancer cells with the most adaptable DNA stemline(s) grow faster, and eventually form a tumor Fujimoto et al 1991) have indicated that patients with aneuploidy have poorer prognosis than those with diploidy, whereas little information is available concerning the relationship between prognosis and DNA heterogeneity. Since patients with the DNA heterogeneity always have aneuploidy, it is reasonable to speculate that multiple aneuploidy may be present in such patients and that the prognosis of patients with DNA heterogeneity may be poorer than those with DNA homogeneity.…”
Section: Discussionmentioning
confidence: 99%